Colorectal cancer screening practices of primary care providers: Results of a national survey in Malaysia - Mohamed Yusoff, Harmy; Daud, Norwati; Norhayati, Noor Mohd (2014)
The incidence of colorectal cancer has been increasing in many Asian countries including Malaysia during the past few decades. A physician recommendation has been shown to be a major factor that motivates patients to undergo screening. The present study objectives were to describe the practice of colorectal cancer screening by primary care providers in Malaysia and to determine the barriers for not following recommendations. In this cross sectional study involving 132 primary care providers from 44 Primary Care clinics in West Malaysia, self-administered questionnaires which consisted of demographic data, qualication, background on the primary care clinic, practices on colorectal cancer screening and barriers to colorectal cancer screening were distributed. A total of 116 primary care providers responded making a response rate of 87.9%. About 21% recommended faecal occult blood test (FOBT) in more than 50% of their patients who were eligible. The most common barrier was “unavailability of the test”. The two most common patient factors are “patient in a hurry” and “poor patient awareness”. This study indicates that colorectal cancer preventive activities among primary care providers are still poor in Malaysia. This may be related to the low availability of the test in the primary care setting and poor awareness and understanding of the importance of colorectal cancer screening among patients. More awareness programmes are required for the public. In addition, primary care providers should be kept abreast with the latest recommendations and policy makers need to improve colorectal cancer screening services in health clinics.